2014
DOI: 10.1038/bjc.2014.328
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of acrylamide and endometrial cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort

Abstract: Background:Three prospective studies have evaluated the association between dietary acrylamide intake and endometrial cancer (EC) risk with inconsistent results. The objective of this study was to evaluate the association between acrylamide intake and EC risk: for overall EC, for type-I EC, and in never smokers and never users of oral contraceptives (OCs). Smoking is a source of acrylamide, and OC use is a protective factor for EC risk.Methods:Cox regression was used to estimate hazard ratios (HRs) for the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…The role of acrylamide on endometrial and ovarian cancers has been the object of a recent debate . In this updated review, we were able to include additional data from the NHS and EPIC (for endometrial cancer only) studies . Still, summary results were close to those of our previous report confirming, overall, an absence of association, but a moderate increase in risk in the subgroup of never smoking women.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The role of acrylamide on endometrial and ovarian cancers has been the object of a recent debate . In this updated review, we were able to include additional data from the NHS and EPIC (for endometrial cancer only) studies . Still, summary results were close to those of our previous report confirming, overall, an absence of association, but a moderate increase in risk in the subgroup of never smoking women.…”
Section: Discussionsupporting
confidence: 64%
“…The findings reported by different studies were generally not heterogeneous, and results were confirmed when only cohort investigation were retained in the analyses. The total number of cancer cases included in this updated meta‐analysis was approximately doubled by including the new data released over the last 5 years, mainly from large prospective cohort studies . Thus, we were able to examine a higher number of cancer sites, as well as to achieve an increased statistical power – with, therefore, narrower CIs for several estimates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the EPIC study, a large prospective study enrolling over 500 000 men and women from 10 European countries between 1992 and 1998, the relation between AA intake and cancer risk was investigated on 341 oesophageal cancers, 865 adenocarcinomas of the exocrine pancreas, 1 191 epithelial ovarian cancers, and 1 382 endometrial cancers identified after a mean follow-up of 11 years (Obón-Santacana et al, 2013;Luján-Barroso et al, 2014;Obón-Santacana et al, 2014, 2015. In this study, food and alcohol consumption was assessed at cohort enrolment by country-specific validated FFQs.…”
Section: Dietary Studies and Cancermentioning
confidence: 99%